IMPROVING ISLAMIC ECONOMIC INSTITUTIONS THROUGH EMPOWERING HUMAN RESOURCES MANAGAMENT (HRM) BASED ON IBNU KHALDUN’S THOUGHTS - Hasan Al Banna (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2019)
ABSTRACTIbnu Khaldun in his masterpiece of Muqaddimah rationalizations  led us to understand how organizations can fall or be led to decline, not so much due to the external forces at work but rather due to the internal forces, which in today’s management views is something within our control.  Everyone within the organization should be given their due respect and worth so that they could work together to ensure the success of the organization.  In this age and time, justice must be seen to be done in order to create an orderly and harmonious society. Ibn Khaldun pointed out correctly when he compared and contrast the marked difference between the simple and pastoral life of the Bedouins and those of the sedentary society of whom the latter’s decline was due to internal factors such as greed and excesses that led to their decline and eventually the downfall of the Muslim empires. In the end of the day, based on Ibnu Khaldun’s thougts, this study is potentially useful to increase knowledge about the contribution of Islam in Islamic economic institution management. This will be an important reference source for those who learn Islam and management for those who will conduct further research in this field.Keyword: Islamic economic institutions; empowering; HRM.